Multiplex real-time PCR assays for the prediction of cephalosporin, ciprofloxacin and azithromycin antimicrobial susceptibility of positive Neisseria gonorrhoeae nucleic acid amplification test samples. (24th August 2020) - Peterson, S W; Martin, I; Demczuk, W; Barairo, N; Naidu, P; Lefebvre, B; Allen, V; Hoang, L; Hatchette, T F; Alexander, D; Tomas, K; Trubnikov, M; et al.
Abstract: Background: The incidence of antimicrobial-resistant Neisseria gonorrhoeae (GC) is rising in Canada; however, antimicrobial resistance (AMR) surveillance data are unavailable for infections diagnosed directly from clinical specimens by nucleic acid amplification tests (NAATs), representing over 80% of diagnoses. We developed a set of 10 improved molecular assays for surveillance of GC-AMR and prediction of susceptibilities in NAAT specimens. Methods: Multiplex real-time PCR (RT–PCR) assays were developed to detect SNPs associated with cephalosporin ( ponA, porB, mtrR −35delA, penA A311V, penA A501, N513Y, G545S), ciprofloxacin ( gyrA S91, parC D86/S87/S88) and azithromycin [23S (A2059G, C2611T), mtrR meningitidis-like promoter] resistance. The assays were validated on 127 gonococcal isolates, 51 non-gonococcal isolates and 50 NAATs with matched culture isolates. SNPs determined from the assay were compared with SNPs determined from in silico analysis of WGS data. MICs were determined for culture isolates using the agar dilution method. Results: SNP analysis of the 50 NAAT specimens had 96% agreement with the matched culture RT–PCR analysis. When compared with MICs, presence of penA A311V or penA A501 and two or more other SNPs correlated with decreased susceptibility and presence of three or more other SNPs correlated with intermediate susceptibility to cephalosporins; presence of any associated SNP correlated with ciprofloxacin or azithromycin resistance. NAAT-AMR predictions correlated with matched-culture cephalosporin, ciprofloxacin and azithromycin MICs at 94%, 100% and 98%, respectively. Conclusions: We expanded molecular tests for N. gonorrhoeae AMR prediction by adding new loci and multiplexing reactions to improve surveillance where culture isolates are unavailable.